2020
DOI: 10.2147/bctt.s277588
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Study on Clinical and Pathological Responses to Neoadjuvant Chemotherapy in Breast Carcinoma</p>

Abstract: Aim and objectives: To assess the effectiveness of neo-adjuvant chemotherapy and its impact on the clinical and pathological response in locally advanced breast cancer. To compare molecular subtypes of breast cancer with response to neo-adjuvant chemotherapy. Patients and methods: This was a prospective study on patients who received neoadjuvant chemotherapy for breast carcinoma for a 3-year period. A total of 60 patients who presented with locally advanced breast cancer (LABC) were treated with neoadjuvant ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
0
5
0
3
Order By: Relevance
“…However, in India, 76% of the patients had either complete or partial responses after treatment. 29 The discrepancy could result from improved infrastructure in India compared to the rural areas of Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…However, in India, 76% of the patients had either complete or partial responses after treatment. 29 The discrepancy could result from improved infrastructure in India compared to the rural areas of Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological response is the endpoint for assessing tumor response to NAC. Complete pathological response is the expected therapeutic outcome, because it can keep the patient from relapse (Kunnuru et al, 2020;Parekh et al, 2015). Tumor response to NAC also depends on the molecular subtype of the cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in the study conducted by Kunnuru et al showed that patients with luminal type had a higher percentage of complete response and partial response when compared with TNBC and HER2 subtypes. [13] Another study conducted by Yarso et al also showed that patients with the luminal subtype had almost the same neoadjuvant chemotherapy response rates as patients with the HER-2 subtype, but both still had a better response than breast cancer patients with the triple negative subtype. [14] The contradictive results in this study can be caused by various factors, including the relatively small number of samples in this study and differences in the study population, as well as the sampling period.…”
Section: Discussionmentioning
confidence: 99%